h - Brake, Laurel; Kaul, Chandrika; Turner, Mark W.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This volume is the first scholarly treatment of the News of the World from news-rich broadsheet to sensational tabloid. Contributors uncover new facts and discuss a range of topics including Sunday journalism, gender, crime, empire, political cartoons, the mass market, investigative techniques and the Leveson Inquiry.
Keywords: History; Industries; History, Modern; Great Britain -- History; Civilization -- History; Social history; Journalism; History; Cultural History; History of Britain and Ireland; Modern History; Social History; Industries; Journalism; Electronic books